Local Classical Solutions to the Equations of Relativistic Hydrodynamics (Journal of Partial Differential Equations, 2001)
In this paper, we prove that the convexity of the negative thermodynamical entropy of the equations of relativistic hydrodynamics for ideal gas keeps its invariance under the Lorentz transformation if and only if the local sound speed is less than the light speed in vacuum. Then a symmetric form for the equations of relativistic hydrodynamics is presented and the local classical solution is obtained. Based on this, we prove that the nonrelativistic limit of the local classical solution to the relativistic hydrodynamics equations for relativistic gas is the local classical solution of the Euler equations for polytropic gas.
Keywords: Relativistic hydrodynamics; convex entropy; local classical solution; nonrelativistic limit